High-resolution mapping of transcriptional dynamics across tissue development reveals a stable mRNA–tRNA interface - Schmitt, Bianca M.; Rudolph, Konrad L.M.; Karagianni, Panagiota; Fonseca, Nuno A.; White, Robert J.; Talianidis, Iannis; Odom, Duncan T.; Marioni, John C.; Kutter, Claudia (Genome Research, 2014)
The genetic code is an abstraction of how mRNA codons and tRNA anticodons molecularly interact during protein synthesis; the stability and regulation of this interaction remains largely unexplored. Here, we characterized the expression of mRNA and tRNA genes quantitatively at multiple time points in two developing mouse tissues. We discovered that mRNA codon pools are highly stable over development and simply reflect the genomic background; in contrast, precise regulation of tRNA gene families is required to create the corresponding tRNA transcriptomes. The dynamic regulation of tRNA genes during development is controlled in order to generate an anticodon pool that closely corresponds to messenger RNAs. Thus, across development, the pools of mRNA codons and tRNA anticodons are invariant and highly correlated, revealing a stable molecular interaction interlocking transcription and translation.
10.1101/gr.176784.114